Development mechanism of local corrosion pit in X80 pipeline steel under flow conditions. (June 2020) - Tan, Zhuowei; Zhang, Dalei; Yang, Liuyang; Wang, Zhenbo; Cheng, Frank; Zhang, Mingyang; Jin, Youhai; Zhu, Shidong
Abstract: In this paper, local corrosion pits were stimulated by arc defect pits (ADP) of different sizes. The corrosion of specimens was tested in high-speed flow CO2 -saturated NACE solution. Electrochemical corrosion characteristics were monitored online. The characteristics of corrosion scale were then investigated by SEM and Raman spectroscopy. The results showed deepening and expansion of corrosion pits will occur at the same time under flow conditions for shallow pits. The development of corrosion pits at certain depth led to formation of complete corrosion scale, which inhibited further corrosion. As corrosion pits deepened, expansion process decreased and deepening rates accelerated. In-depth analysis suggested that corrosion rates were mainly affected by mass transfer rate and integrity of formed corrosion scale. Highlights: The interaction between the deepening process of the local corrosion pit and the flow is simulated. Proved the corrosion process of different regions of uneven surface is different under flow condition. Evaluated the influence of development stage of local corrosion pit on corrosion process, and the process of deepening and expanding corrosion pit is clarified.